Towards elderly social integration using a multimodal human-computer interface - Teixeira, V. D.; Pires, C. G.; Pinto, F. M.; Freitas, J.; Dias, M. S.; Rodrigues, E. M. (Proceedings of the 2nd International Living Usability Lab Workshop on AAL Latest Solutions, Trends and Applications - AAL, (BIOSTEC 2012), 2012)
This paper presents a multimodal prototype application that aims to promote the social integration of the elderly. The application enables communication with their social network through conferencing and social media services, using natural interaction modalities, like speech, touch and gestures. We begin by discussing the requirements and design guidelines that were taken into account for the development of the prototype. We also present the key elements of the development stage and the results of a usability study conducted with ten elderly volunteers. The usability study reveals that such a multimodal solution can simplify accessibility to the considered services. Results indicate that this system is simpler, more natural and more enjoyable than the current user interfaces. Furthermore, the natural interaction modalities of the proposed prototype, allow elderly to be more efficient and have a better user experience, thus contributing with an easier and faster way for this population to join the information era.